PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VII SMPN 29 PADANG - Furnanda, Siska; Longgom, Minora; Harisman, Yulyanti (Pendidikan Matematika, 2013)
Background of the research is the result of matematis concept low student understanding. Purpose of the research is the find result matematis concept of the student with used model cooperative learning type Think Pair Share more than effective from the result conventional learning. Type of the research is experimental research. Population of the research all of the students grade VII SMPN 29 Padang in year 2012/2013. The process of selecting sampling by cluster random sampling. Of the research is essay. Instrument doing analysis of data used t-test. However the result of Â the model cooperative learning type Think Pair Share Â suitable more than conventional learning for student grade VII SMPN 29 Padang.